Cartografia decolonial da memória de gênero: resistências e mediações em histórias de vida de mulheres migrantes-pioneiras de Pato Branco (PR) - Suttili, Jozieli Camila Cardenal (2024)
While experience in decolonial translation, this thesis is an ethnographic-cartographic study based on the life stories of womens migrant-pioneers. The starting point refers to the migratory flow and pioneer expansion destined for the southwest region of Paraná between the 1930s and 1940s, resulting from the March to the West and the creation of the General Ozório National Agricultural Colony (CANGO), colonizing policies by the Estado Novo. For identify how women migrant-pioneers experienced and resisted the oppressions on their bodies and minds, resulting from this socio-historical period, this research mobilizes stories of twelve (12) women rememberers to analyse colonialities, mediations and resistance in the colonization process of Pato Branco (PR). As a result, was developed a cartographic method called gender memory, which translates gender colonialities contained in sociogenesis of local memory, based on the experiences, invisibilities and struggles narrated for womens. The decolonial epistemology as a theoretical-methodological compass made it possible to deconstruct silences legitimized by official history.